2001
DOI: 10.1111/j.8755-8920.2001.450305.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 Up‐Regulates the Oxytocin Receptor in Cultured Uterine Smooth Muscle Cells

Abstract: IL-6 up-regulates uterine OTR mRNA expression and binding capacity in cultured human myocytes most likely through tyrosine and serine phosphorylation pathways involving the nuclear factor STAT-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 0 publications
1
47
0
2
Order By: Relevance
“…IL-6 promotes synchronous myometrial contraction via PG synthesis and expression of oxytocin and its receptor. [32][33][34][35] Furthermore, IL-6 2/2 mice showed impaired leukocyte accumulation, suggesting that IL-6 also plays a role in leukocyte recruitment. 36 Two CXC family chemokines (CXCL1 and CXCL8) are well known for their strong chemoattractant activity on neutrophils, and their expression in human myometrium during spontaneous labour was reported and confirmed by many research groups.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 promotes synchronous myometrial contraction via PG synthesis and expression of oxytocin and its receptor. [32][33][34][35] Furthermore, IL-6 2/2 mice showed impaired leukocyte accumulation, suggesting that IL-6 also plays a role in leukocyte recruitment. 36 Two CXC family chemokines (CXCL1 and CXCL8) are well known for their strong chemoattractant activity on neutrophils, and their expression in human myometrium during spontaneous labour was reported and confirmed by many research groups.…”
Section: Discussionmentioning
confidence: 99%
“…At term, estrogen and interleukin-6 have been suggested to modulate oxytocin receptor gene expression and both are elevated at the time of parturition (Young et al 1997). Interleukin-1 down-regulates uterine oxytocin receptor in a time-and dose-dependent fashion (Rauk & Friebe-Hoffmann 2000). Regardless of the mechanisms controlling the cardiac oxytocin system, it is interesting to note that inhibited cardiac oxytocin or oxytocin receptors in rat heart at term is consistent with increased heart rate and force of contraction observed in term pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on such comparative analyses as well as the clinical relationship between intrauterine infection and the onset of preterm birth, many investigators hypothesized that OTR transcription would be up-regulated by proinflammatory cytokines such as interleukin (IL)-1 and IL-6 via activation of the binding elements for nuclear factor (NF)-IL-6 or Stat3 (Inoue et al 1994). In cultured uterine smooth muscle cells obtained at Caesarean section, IL-6 up-regulates OTR expression in a tyrosine kinasedependent manner (Rauk et al 2001). However, Schmid et al (2001) reported that both IL-1 and IL-6 down-regulate the transcription of a reporter gene connected to the OTR gene promoter transfected into a human myometrial cell line (ULTR).…”
Section: The Otr Gene and Its Transcriptional Regulationmentioning
confidence: 99%